The impact of the corporate social responsibility on the reputation of companies - Zinchenko, A.; Naumov, V. (Baltic International Academy, 2019)
Розглядаються глобальні тренди сучасності, які дають поштовх до впровадження і подальшого розвитку соціальної відповідальності компаній. На основі численних досліджень аналізується позитивний вплив політики соціальної відповідальності на компанію (інвестиційну привабливість, лояльність споживачів і працівників, її вартість) та її репутацію. На основі аналізу і порівняння методології міжнародних рейтингів репутації виокремлені складові соціальної відповідальності, які мають найбільший вплив на зростання репутації компанії. // Global trends of today are considered, which give impetus to the introduction and further development of corporate social responsibility. Based on numerous studies, the positive impact of social responsibility policy on the company (investment attractiveness, customer and employee loyalty, its value) and its reputation is analyzed. Based on the analysis and comparison of the methodology of international reputation ratings, the components of social responsibility that have the greatest impact on the growth of the company's reputation are identified.
Keywords: КСВ; репутація; стійкість; CSR; reputation; stability